IL-9 Deficiency Promotes Pulmonary Th17 Response in Murine Model of Pneumocystis Infection - Li, Ting; Rong, Heng-Mo; Zhang, Chao; Zhai, Kan; Tong, Zhao-Hui (Frontiers in Immunology, 2018)
Introduction: Pneumocystis pneumonia (PCP) remains a severe complication with high mortality in immunocompromised patients. It has been well accepted that CD4+ T cells play a major role in controlling Pneumocystis infection. Th9 cells were the main source of IL-9 with multi-faced roles depending on specific diseases. It is unclear whether IL-9/Th9 contributes to the immune response against PCP. The current study was aim to explore the role of IL-9 and the effect of IL-9 on Th17 cells in murine model of PCP. Materials and Methods: Mice were intratracheally injected with 1×106 Pneumocystis organisms to establish the murine model of Pneumocystis infection. Pneumocystis burden was detected by Taqman real-time PCR. Using IL-9 deficient (IL-9‒/‒) mice, flow cytometry, real-time PCR and ELISA were conducted to investigate the immune function related to Th17 response in defense against Pneumocystis infection. Results: Reduced Pneumocystis burden was observed in lungs in IL-9‒/‒ mice compared with WT mice at 3 week post infection. IL-9‒/‒mice exhibited stronger Th17 immune responses than WT PCP mice through flow cytometer and real-time PCR. ELISA revealed higher levels of IL-17 and IL-23 in BALF from IL-9‒/‒ mice than WT mice. And IL-9 deficiency promoted Th17 differentiation from CD4+ naïve T cells. IL-17A neutralization increased Pneumocystis burden in IL-9‒/‒ mice. Conclusions: Although similar basic clearance of Pneumocystis organisms was achieved in both WT and IL-9‒/‒ PCP mice, IL-9 deficiency could lower Pneumocystis organism burden and promote pulmonary Th17 cells response in the early stage of infection.